Love, sex, and lasting relationships - Ingram, Chip (Baker Books, 2004)
Why do so many relationships go wrong? At first, that true love seems perfect, the answer to all your dreams. But with time and familiarity, the tension mounts. You're disappointed and doubtful. Before long, love crumbles and you're left alone or stuck in a meaningless marriage.